2014
DOI: 10.3892/ijmm.2014.1713
|View full text |Cite
|
Sign up to set email alerts
|

Celecoxib regulates apoptosis and autophagy via the PI3K/Akt signaling pathway in SGC-7901 gastric cancer cells

Abstract: Gastric cancer, one of the most common malignancies worldwide, typically has a poor prognosis and poor survival rate. Previous studies have investigated the chemopreventive effect of celecoxib. In the present study, the SGC-7901 human gastric cancer cell line was utilized to examine the chemopreventive mechanisms of celecoxib. The inhibition of cell proliferation was determined using MTT assay, cell apoptosis was monitored by terminal deoxynucleotidyl transferase-mediated dUTP nick end-labeling (TUNEL) and flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
51
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 36 publications
1
51
0
Order By: Relevance
“…Focusing on dysregulation mRNAs through GO and Pathway analysis, the GO results suggested the functions of significant differences in the aspects of immune functions, metabolism and cellular functions, the significant differences in the pathways mainly focus on cancer-related pathways such as 'PI3K-Akt signaling pathway, Wnt signaling pathway, pathways in cancer and small cell lung cancer'. Many pathway-related analysis of the GC significant difference genes, Liu et al (41) and Ren et al (42), also found 'PI3K-Akt signaling pathway and Wnt signaling pathway' were related with GC cell functions.…”
Section: Discussionmentioning
confidence: 98%
“…Focusing on dysregulation mRNAs through GO and Pathway analysis, the GO results suggested the functions of significant differences in the aspects of immune functions, metabolism and cellular functions, the significant differences in the pathways mainly focus on cancer-related pathways such as 'PI3K-Akt signaling pathway, Wnt signaling pathway, pathways in cancer and small cell lung cancer'. Many pathway-related analysis of the GC significant difference genes, Liu et al (41) and Ren et al (42), also found 'PI3K-Akt signaling pathway and Wnt signaling pathway' were related with GC cell functions.…”
Section: Discussionmentioning
confidence: 98%
“…Similarly, Cho et al (20) demonstrated the anti-cancer effect of celecoxib on GC cells (AGS and MKN-45) by regulating cell-cycle arrest and apoptosis. In addition, Liu et al (11) suggested that celecoxib induced apoptosis through the mitochondrial and death receptor pathways in GC cells. These results indicated that a low dose of celecoxib may have a chemopreventive function in the development of GC by regulating cell cycle and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to aspirin, celecoxib, a cyclooxygenase-2 (COX-2) inhibitor, has been demonstrated to be involved in uncontrolled cell proliferation, apoptosis, angiogenesis and metastasis (9,10). Previous studies have suggested that celecoxib is able to induce cell apoptosis through the phosphoinositide 3 kinase/Akt signaling pathway (11) and to inhibit invasion through the adenine nucleotide translocator-dependent signaling pathway in GC cells (12). In addition, celecoxib has been reported to be able to prevent the development of GC in rats (13).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated that celecoxib and caffeine induced autophagy through inhibition of the PI3K/ATK signaling pathway (17,18). The PI3K/AKT signaling pathway is widely utilized in normal and abnormally activated cells, such as in cancer cells (19).…”
Section: Introductionmentioning
confidence: 99%